DESAIN AREA DERMAGA APUNG SEBAGAI PENUNJANG WISATA DI BANUA ANYAR BANJARMASIN - Rahman, Noorudien Dwi; Rahman, Akbar; Mutia, Indah (UNIVERSITAS LAMBUNG MANGKURAT, 2023)
The geographical location of the Martapura river basin in Banua Anyar Village is quite strategic, moreover, this area is one of the tourist areas in Banjarmasin which is also the target of developing a tourist area by the South Kalimantan Environmental Service in the Martapura Asri River program. However, currently, there is a lack of supervision and maintenance, resulting in many river problems and public facilities that are not functioning properly in the culinary tourism area on the Martapura River. Existing facilities are considered not yet available to solve river problems and do not meet the needs of visitors so the design of tourist river support facilities is to meet the needs of visitors. Writing aims to design a floating pier at the location of the river access center on the banks of the Martapura river in Banua Anyar Village. Through direct observation surveys and documentation at the wharf design location as the basis for the design. The approach applied is an environmentally friendly architecture (Green Architecture) with eco enzymes as a mixed medium in river waste around the wharf. Designers are focused on the functional form and structural strength of disaster response in river watersheds so that they can more easily implement designs that are following river problems in the surrounding area. The results of this writing formulate the overlapping concept of the functions of public facilities between the problems of overcoming the density of land health insurance routes and environmental pollution due to residents' waste. The planned facilities include 1) a Floating Pier as an area of ​​the main function of the river bank; 2) Providing space facilities for washing clothes as well as environmentally friendly public toilets; 3) Developing and improving the area around the site by updating other facilities.